Repeated Communication and Echolalia in Autism (A Case Study) - Surya Wijaya Purnama; Utami Dewi (Jurnal Basicedu, 2022)
This study aims to examine the communication phenomenon of autistic children who are influenced by echolalia. One of the difficulties faced by autistic children in communicating, especially for children who experience severe barriers, is in mastering language and speech. This study uses a qualitative approach, in which the researcher describes the existing reality. The main informants in this study were a teacher at the Center for Emotional Focus Therapy and a teacher at the Behavior Therapy Center. The results showed that learning to communicate nonverbally with autistic children was more dominant by instilling language concepts through visual media by means of the teacher asking questions and the children answering things with their abilities. The teacher helps by showing visual pictures and asking autistic children to imitate them. As for verbal autistic children, both teachers emphasize adding or expanding vocabulary. The difficulty of autistic children in communicating is caused by having language disorders (verbal and nonverbal), even though language is the main communication medium. They often have difficulty communicating their desires both verbally (oral/speaking) and nonverbally (gestures/gestures and writing). Most of them can speak, using short sentences with simple vocabulary but their vocabulary is limited.